EVALUAREA HIDROLOGICĂ A BAZINULUI r. PRUT - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2009)
The riverside of the Prut river has an important role in the development of the small and medium towns in the aria by means of water reserves, ecological state, degree of disruption. The infi nitesimal fl ow of the small rivers become vulnerable in the freshet periods and can cause immense fl oods.